2015
DOI: 10.1167/tvst.4.2.10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stimulus Size on the Reliable Stimulus Range of Perimetry

Abstract: Purpose: Automated perimetry uses a 3.5 log unit (35dB) range of stimulus contrasts to assess function within the visual field. Using 'Size III' stimuli (0.438), presenting stimuli within the highest 15dB of available contrast may not increase the response probability at locations damaged by glaucoma, due to retinal ganglion cell response saturation. This experiment examines the effect of instead using 'Size V' (1.728) stimuli.Methods: Luminance increment thresholds for circular spot stimuli of each stimulus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 34 publications
5
54
0
3
Order By: Relevance
“…2B), which may be accredited to the greater number of response elements recruited with a larger stimulus size compensating for the reduced density. 28 This is also consistent with the results of a previous study, 51 which suggests better response characteristic can be attained in areas with sensitivity below the measurement floor with a larger stimulus size. Therefore, selection of a stimulus size within the spatial summation area but not smaller than truly necessary may maximize the signal-to-noise ratio.…”
Section: Practical Implications Of Structure-function Correlation Witsupporting
confidence: 91%
“…2B), which may be accredited to the greater number of response elements recruited with a larger stimulus size compensating for the reduced density. 28 This is also consistent with the results of a previous study, 51 which suggests better response characteristic can be attained in areas with sensitivity below the measurement floor with a larger stimulus size. Therefore, selection of a stimulus size within the spatial summation area but not smaller than truly necessary may maximize the signal-to-noise ratio.…”
Section: Practical Implications Of Structure-function Correlation Witsupporting
confidence: 91%
“…In another study the investigators found no evidence that use of a size V stimulus significantly decreased the lower limit of the reliable stimulus range beyond 15–19 dB (Gardiner et al, 2015); however, using a size V stimulus resulted in a higher sensitivity at the same location. For instance, a test location that reached a sensitivity value of 15 dB with size III may reveal a sensitivity of 20 dB when tested with a size V stimulus.…”
Section: Detection Of Visual Field Progressionmentioning
confidence: 99%
“…Using Size V (1.72° diameter) stimuli instead of the more conventional Size III (0.43° diameter) stimuli reduces variability at any given location, 15 but this appears to be driven solely by the increase in sensitivity caused by use of larger stimuli, 16 implying that it postpones but does not prevent the point at which variability is too high to be able to distinguish true change from noise in a clinic situation. It may be more efficient to present larger stimuli if the test subject does not respond to a 15-dB Size III stimulus, as is done by the Heidelberg Edge Perimeter (Heidelberg Engineering, Heidelberg, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility would be to use larger stimuli throughout the range to reduce variability 15 and extend the range of severities over which reliable measurements could be obtained. 16,17 Size threshold perimetry, whereby stimulus size is altered rather than contrast, may also extend the dynamic range without increasing variability, 18 although this would require more extensive modifications to clinical perimeters so as to meet the need for a sufficient number of different stimulus sizes.…”
Section: Discussionmentioning
confidence: 99%